Between ‘citizen of the world’ and ‘patriot’: Kant’s Pragmatic Cosmopolitanism vs. John S. Mill’s Political Utilitarianism - Salikov, Alexey (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Kant is considered one of the main theorists of Enlightenment cosmopolitanism: it reaches its apotheosis in his formulation of cosmopolitan law, accumulating practically the entire complex of ideas associated with cosmopolitanism of 18th century. However, even if cosmopolitanism was one of mainstream ideas in political thought of Enlightenment, already in the early 19th century the cosmopolitan idea faced with the idea of a nation state and local patriotism, the Enlightenment idea of world unity and world citizenship lost much of its appeal to the political thinkers of that time and their contemporaries. Nevertheless, despite significant rise of the national idea after 1789, there was no decisive break with the cosmopolitan views in the political thought in the following period of time. On the contrary, cosmopolitanism remained to be one of the most important political ideas throughout the 19th century.  The main purpose of my paper is to answer the question on the role of Kant’s cosmopolitanism in the process of development of political thought in the 19th century on the example of John S. Mill’s political utilitarianism. In my paper, I will show that despite Mill’s criticism of Kantian ethics, his political philosophy shares with Kant the common pathos of Enlightenment humanism and has some important parallels with Kantian theory of cosmopolitanism. This suggests that Kant's pragmatic anthropology, his thoughts on the civil and political development of mankind, in particular his concept of world citizen, could serve as one of the sources of political ideas of utilitarianism.